Sistem Penunjang Keputusan Pemilihan Model Stainless steel untuk Kitchen Set dengan Metode AHP - Abdullah, Syamsun Nahar; Fitri, Iskandar; Aldisa, Rima Tamara (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The purpose of this study is to determine the selection of the best Stainless steel model for the Kitchen Set and can utilize the area in the kitchen room well, because the role of the kitchen set in a house is not just a room filled with spices and cooking utensils, but with a kitchen set that Ideally, the activities carried out will feel more comfortable. The method in this study uses the Analytical Hierachy Process (AHP) method where AHP is a structured technique used for organization and decision analysis and can assist in the representation of the most appropriate approach for quantifying the weights of each criterion. By using the AHP method, it produces a list of alternatives and determines the selection of models and also this system makes it easy to assess the criteria and quality of the best Stainless steel for use in Kitchen Sets.
Keywords: Decision Support System; Kitchen Sets; stainless steel; Chromium; AHP